2014
DOI: 10.1039/c4tc01629g
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of zinc oxide onto and into P3HT for hybrid photovoltaics

Abstract: ALD ZnO precursors diffuse into the disordered regions of a P3HT film yielding the bulk heterojunction morphology for hybrid photovoltaics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
54
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 42 publications
(52 reference statements)
7
54
2
Order By: Relevance
“…This phenomenon was used previously for processing hybrid organic/inorganic films for varying applications [3][4][5][6][7]. For example, we recently showed that the diffusion of diethyl zinc (DEZ) and water into P3HT films and the in-situ reaction leads to the deposition of ZnO nanocrystals inside the amorphous regions of P3HT [7]. This sub-surface deposition of ZnO was used to fabricate hybrid organic/inorganic photovoltaic films.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…This phenomenon was used previously for processing hybrid organic/inorganic films for varying applications [3][4][5][6][7]. For example, we recently showed that the diffusion of diethyl zinc (DEZ) and water into P3HT films and the in-situ reaction leads to the deposition of ZnO nanocrystals inside the amorphous regions of P3HT [7]. This sub-surface deposition of ZnO was used to fabricate hybrid organic/inorganic photovoltaic films.…”
Section: Introductionmentioning
confidence: 94%
“…However, when applying metal-oxide ALD onto organic materials with no surface reactivity, the precursors diffuse into the organic film and generate a sub-surface deposition of the metal oxide. This phenomenon was used previously for processing hybrid organic/inorganic films for varying applications [3][4][5][6][7]. For example, we recently showed that the diffusion of diethyl zinc (DEZ) and water into P3HT films and the in-situ reaction leads to the deposition of ZnO nanocrystals inside the amorphous regions of P3HT [7].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…While strategies to prepare hybrid photovoltaics i.e. where the oxide acts as both an active material and the electron transport layer have had limited success [19][20][21][22] the incorporation of a nanostructured electron acceptor here, using simple device structures processed in ambient, is shown to improve performance. Unlike previous reports where multistep patterning was required or where non-standard conjugated materials utilized [23] here we describe the preparation of bulk heterojunction photovoltaic devices using the commonly used, widely available active materials poly(3-hexylthiophene-2,5-diyl) (P3HT) -indene-C 60 bisadduct (IC 60 BA) using planar and nanostructured ZnO electron extracting layers and report on the device improvements enabled by incorporating nanorod electrodes and the impact these electrodes have on the optimum active layer composition.…”
Section: Introductionmentioning
confidence: 99%